Evaluation in mice of a conjugate vaccine for cholera made from Vibrio cholerae O1 (Ogawa) O-specific polysaccharide. - Mohammad Murshid Alam; Megan Kelly Bufano; Peng Xu; Anuj Kalsy; Y Yu; Y Wu Freeman; Tania Sultana; Md Rasheduzzaman Rashu; Ishaan Desai; Grace Eckhoff; Daniel T Leung; Richelle C Charles; et al. (Public Library of Science (PLoS), 2014)
BACKGROUND:Protective immunity against cholera is serogroup specific. Serogroup specificity in Vibrio cholerae is determined by the O-specific polysaccharide (OSP) of lipopolysaccharide (LPS). Generally, polysaccharides are poorly immunogenic, especially in young children. METHODOLOGY:Here we report the evaluation in mice of a conjugate vaccine for cholera (OSP:TThc) made from V. cholerae O1 Ogawa O-Specific Polysaccharide-core (OSP) and recombinant tetanus toxoid heavy chain fragment (TThc). We immunized mice intramuscularly on days 0, 21, and 42 with OSP:TThc or OSP only, with or without dmLT, a non-toxigenic immunoadjuvant derived from heat labile toxin of Escherichia coli. PRINCIPAL FINDINGS:We detected significant serum IgG antibody responses targeting OSP following a single immunization in mice receiving OSP:TThc with or without adjuvant. Anti-LPS IgG responses were detected following a second immunization in these cohorts. No anti-OSP or anti-LPS IgG responses were detected at any time in animals receiving un-conjugated OSP with or without immunoadjuvant, and in animals receiving immunoadjuvant alone. Responses were highest following immunization with adjuvant. Serum anti-OSP IgM responses were detected in mice receiving OSP:TThc with or without immunoadjuvant, and in mice receiving unconjugated OSP. Serum anti-LPS IgM and vibriocidal responses were detected in all vaccine cohorts except in mice receiving immunoadjuvant alone. No significant IgA anti-OSP or anti-LPS responses developed in any group. Administration of OSP:TThc and adjuvant also induced memory B cell responses targeting OSP and resulted in 95% protective efficacy in a mouse lethality cholera challenge model. CONCLUSION:We describe a protectively immunogenic cholera conjugate in mice. Development of a cholera conjugate vaccine could assist in inducing long-term protective immunity, especially in young children who respond poorly to polysaccharide antigens.